MANAGEMENT OF RESIDUAL REFRACTIVE ERROR AFTER CATARACT PHACOEMULSIFICATION. PART 2. INTRAOCULAR APPROACHES - K. B. Pershin; N. F. Pashinova; A. Iu. Tsygankov; E. P. Gurmizov; L. V. Batalina (Oftalʹmologiâ)
The review presents an  analysis  of the  literature  data  on  the  methods of surgical  correction of residual  refractive  error after cataract phacoemulsification. Keratorefractive and intraocular approaches are  considered in details.  A comparison of the  efficacy and  safet y  of different groups   of methods on  the  example  of comparative studies is given.  Historically earlier  keratorefractive methods (laser  vision correction with LASIK and  PRK techniques on intact  eyes,  LASIK after  implantation  of multifocal  IOLs and arcuate keratotomy  after  phaco)  are  indicated  for  the  correction of astigmatic refractive  error and  a small  spherical refractive error. Intraocular methods, including the  replacement of the  IOL  and  «piggyback» IOLs implantation  are  used  to  correct a large spherical refractive error. The introduction  of new  technology, the  implantation  of light-adjustable  IOLs, will  expand  the  existing evidence  and provide greater predictabilit y and efficiency of the  method  of correction of residual  refractive error.